(untitled) (Journal of Universal Science Research, 2023)
In the age of digital communication, an abundance of textual data is generated daily through various channels, such as social media, emails, and chat applications. This wealth of textual information has opened up new avenues for understanding and evaluating the emotional states of individuals. Text analysis, a powerful tool in natural language processing (NLP), has emerged as a valuable method for gaining insights into the emotions, sentiments, and psychological well-being of people. This article explores the method of text analysis and its application in evaluating the emotional state of individuals through textual data.